Advanced biofabrication strategies for skin regeneration and repair. (April 2013) - Pereira, Rúben F; Barrias, Cristina C; Granja, Pedro L; Bartolo, Paulo J
Skin is the largest organ of human body, acting as a barrier with protective, immunologic and sensorial functions. Its permanent exposure to the external environment can result in different kinds of damage with loss of variable volumes of extracellular matrix. For the treatment of skin lesions, several strategies are currently available, such as the application of autografts, allografts, wound dressings and tissue-engineered substitutes. Although proven clinically effective, these strategies are still characterized by key limitations such as patient morbidity, inadequate vascularization, low adherence to the wound bed, the inability to reproduce skin appendages and high manufacturing costs. Advanced strategies based on both bottom-up and top-down approaches offer an effective, permanent and viable alternative to solve the abovementioned drawbacks by combining biomaterials, cells, growth factors and advanced biomanufacturing techniques. This review details recent advances in skin regeneration and repair strategies, and describes their major advantages and limitations. Future prospects for skin regeneration are also outlined.